The lights are still on: the persistence and extraordinary density of the European lightbulb sea squirt Clavelina lepadiformis (Ascidiacea) in the Northwest Atlantic Ocean - Aria S. Lupo; Krystal Rose; Caleb Rose; Timothy J. Pusack; James T. Carlton (Biological Invasions, 2026)

Protracted recovery of long-spined urchin (Diadema antillarum) in the Bahamas - Timothy J. Pusack; Christopher D. Stallings; Mark A. Albins; Cassandra E. Benkwitt; Kurt E. Ingeman; Tye L. Kindinger; Mark A. Hixon (Coral Reefs, 2023)

Predation on oysters is inhibited by intense or chronically mild, low salinity events - Timothy J. Pusack; David L. Kimbro; J. Wilson White; Christopher D. Stallings (Limnology and Oceanography, 2019)
Environmental stress gradients can affect species distributions and interspecific interactions. Because environmental stress depends on both intensity and duration, understanding the consequences of stress requires experiments that simultaneously manipulate both dimensions. In Apalachicola Bay, Florida (U.S.A.) the southern oyster drill ( Stramonita haemastoma ) is a major predator of the eastern oyster ( Crassostrea virginica ). Drill predation appears to be salinity‐dependent: in a recent field study, predation rates were positively correlated with salinity. Salinity in the bay is typically high (> 20) during the dry summer months, conditions that favor both oysters and the drill. However, periodic freshets can dramatically reduce salinity, which inhibits (or kills) drills, but not oysters. In this study, we used field measurements of salinity and drill densities to inform mesocosm experiments. We investigated the specific combinations of intensity and duration of low‐salinity stress that inhibit drill predation. In these experiments, more intense salinity reductions reduced feeding both during and after the low‐salinity stress event. During the event, longer durations (15 d) were necessary for mild salinity reductions (−5) to reduce the feeding rate by the same amount as a short (5 d) exposure of more intense (−10 or −15) salinity reduction. Both conditions may create a predation refuge for oysters, consistent with field observations. Given that the recent collapse of the Apalachicola Bay oyster population was preceded by several years without low‐salinity events to inhibit predation, our results provide a mechanism by which a predator may have contributed to the loss of a historically productive and sustainable fishery.

Integrating larval connectivity with local demography reveals regional dynamics of a marine metapopulation - Darren W. Johnson; Mark R. Christie; Timothy J. Pusack; Christopher D. Stallings; Mark A. Hixon (Ecology, 2018)
Many ocean species exist within what are called marine metapopulations: networks of otherwise isolated local populations connected by the exchange of larval offspring. In order to manage these species as effectively as possible (e.g., by designing and implementing effective networks of marine protected areas), we must know how many offspring are produced within each local population (i.e., local demography), and where those offspring disperse (i.e., larval connectivity). Although there is much interest in estimating connectivity in the relatively simple sense of identifying the locations of spawning parents and their settling offspring, true measures of demographic connectivity that account for among‐site variation in offspring production have been lacking. We combined detailed studies of local reproductive output and larval dispersal of a coral reef fish to quantify demographic connectivity within a regional metapopulation that included four widely spaced islands in the Bahamas. We present a new method for estimating demographic connectivity when the levels of dispersal among populations are inferred by the collection of genetically “tagged” offspring. We estimated that 13.3% of recruits returned to natal islands, on average (95% CI = 1.1–50.3%), that local retention was high on one of the islands (41%, 95% CI = 6.0–97.0%), and that larval connectivity was appreciable, even between islands 129 km apart (mean = 1.6%, 95% CI = 0.20–8.8%). Our results emphasize the importance of properly integrating measurements of production with measurements of connectivity. Had we not accounted for among‐site variation in offspring production, our estimates of connectivity would have been inaccurate by a factor as much as 6.5. At a generational timescale, lifetime offspring production varied substantially (a fivefold difference among islands) and the importance of each island to long‐term metapopulation growth was dictated by both larval production and connectivity. At the scale of our study (local populations inhabiting 5‐ha reefs), the regional metapopulation could not grow without external input. However, an exploratory analysis simulating a network of four marine protected areas suggested that reserves of >65 ha each would ensure persistence of this network. Thus, integrating studies of larval connectivity and local demography hold promise for both managing and conserving marine metapopulations effectively.

Is the lionfish invasion waning? Evidence from The Bahamas - Cassandra E. Benkwitt; Mark A. Albins; Kevin L. Buch; Kurt E. Ingeman; Tye L. Kindinger; Timothy J. Pusack; Christopher D. Stallings; Mark A. Hixon (Coral Reefs, 2017)

Invasive Red Lionfish (Pterois volitans) grow faster in the Atlantic Ocean than in their native Pacific range - Timothy J. Pusack; Cassandra E. Benkwitt; Katherine Cure; Tye L. Kindinger (Environmental Biology of Fishes, 2016)

Competitive interactions for shelter between invasive Pacific red lionfish and native Nassau grouper - Wendel W. Raymond; Mark A. Albins; Timothy J. Pusack (Environmental Biology of Fishes, 2015)

Spatial and temporal patterns of larval dispersal in a coral‐reef fish metapopulation: evidence of variable reproductive success - Timothy J. Pusack; Mark R. Christie; Darren W. Johnson; Christopher D. Stallings; Mark A. Hixon (Molecular Ecology, 2014)
Many marine organisms can be transported hundreds of kilometres during their pelagic larval stage, yet little is known about spatial and temporal patterns of larval dispersal. Although traditional population‐genetic tools can be applied to infer movement of larvae on an evolutionary timescale, large effective population sizes and high rates of gene flow present serious challenges to documenting dispersal patterns over shorter, ecologically relevant, timescales. Here, we address these challenges by combining direct parentage analysis and indirect genetic analyses over a 4‐year period to document spatial and temporal patterns of larval dispersal in a common coral‐reef fish: the bicolour damselfish ( Stegastes partitus ). At four island locations surrounding Exuma Sound, Bahamas, including a long‐established marine reserve, we collected 3278 individuals and genotyped them at 10 microsatellite loci. Using Bayesian parentage analysis, we identified eight parent‐offspring pairs, thereby directly documenting dispersal distances ranging from 0 km (i.e., self‐recruitment) to 129 km (i.e., larval connectivity). Despite documenting substantial dispersal and gene flow between islands, we observed more self‐recruitment events than expected if the larvae were drawn from a common, well‐mixed pool (i.e., a completely open population). Additionally, we detected both spatial and temporal variation in signatures of sweepstakes and Wahlund effects. The high variance in reproductive success (i.e., ‘sweepstakes’) we observed may be influenced by seasonal mesoscale gyres present in the Exuma Sound, which play a prominent role in shaping local oceanographic patterns. This study documents the complex nature of larval dispersal in a coral‐reef fish, and highlights the importance of sampling multiple cohorts and coupling both direct and indirect genetic methods in order disentangle patterns of dispersal, gene flow and variable reproductive success.

Can humans coexist with fishes? - Mark Albins; Allison Evans; Gladys Ismail; Brian Neilsen; Timothy Pusack; Eva Schemmel; Wade Smith; Susanne Stoike; Hiram W. Li; David L. G. Noakes (Environmental Biology of Fishes, 2013)

Threatened fishes of the world: Epinephelus itajara (Lichtenstein, 1822) (Epinephelidae, formerly Serranidae) - Timothy J. Pusack; Rachel T. Graham (Environmental Biology of Fishes, 2009)